Character Formation Through Islamic Religious Education In Early Childhood - Nurul Izzah; Ade Amalia; Siti Mutiah (Yayasan Rahmat Islamiyah, 2023)
The article discusses the role of Islamic religious education and character building through Islamic religious education in early childhood (PAUD). Therefore, the main goal of PAI learning is the formation of personality in students which is reflected in their behavior and mindset in everyday life. Besides that, one of the successes of PAI learning in schools is also determined by the application of appropriate learning methods.